Effect of trypanosome infection on livestock health and production traits in two areas of Togo - Defly, A.; Awuome, K.; Bokovi, K.; D'Ieteren, G.D.M.; Grundler, G.; Handlos, Michael; Itty, P.; Maehl, H.M.; Morkramer, G.; Nagda, S.M.; Rarieya, J.M.; Thorpe, W.R.; et al. (OAU/STRC, 1988)
Presents data on the prevalence, species and intensity of trypanosome infection found in different livestock species, breeds, age groups and management systems for cattle and sheep in the Avetonou area and for sheep and goats in the sokode area, Togo. Evaluates the effect of these trypanosome infections on health and production traits in cattle